2020
DOI: 10.21608/ijma.2020.22101.1078
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Placental Thickness Measurements and Fetal Outcome in Patients with Intrauterine Growth Restriction (IUGR)

Abstract: Background: Placental thickness appears to be a promising parameter for estimation of gestational age of the fetus due to steady increase in placental thickness with gestational age. Aim of the work: To investigate the relationship between placental thickness and fetal outcome in patients with intrauterine growth restriction [IUGR]. Patients and Methods: This study included patients with fetuses diagnosed clinically and by ultrasound as IUGR [estimated fetal weight <10 th percentile for gestational age], singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Our results agree with the study of Adeyekun and Ikubor [12], as they reported that study subjects were 29.1 ± 4.9 years. The mean maternal height was 1.6 ± 0.5 m and 71. kg/m 2 [1]. These results matched with the results of our study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results agree with the study of Adeyekun and Ikubor [12], as they reported that study subjects were 29.1 ± 4.9 years. The mean maternal height was 1.6 ± 0.5 m and 71. kg/m 2 [1]. These results matched with the results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…The thickness of the placenta is closely linked to fetal development and can play a role in the perinatal outcome. The placenta is about 3 cm thick and 15-25 cm in diameter [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations